Alkaloid from Anona reticulata Linnaeus - Cachero, Ma. Luisa G. (Quezon City: College of Pharmacy, University of the Philippines, 1981.)
Many members of the Family Anonaceae have been found to contain alkaloids. Of its 125 species contained in the genus Anona, extensive research have been done on Anona muricata Linn. (soursop) and Anona squamosa Linn. (sugar apple). As early as 1930, Alfredo C. Santos, upon examination of the bark of Anona reticulata L., found that it contains 0.03% anonaine. This alkaloid, melting at 122-123°C, had a formula of C17H16O3N. in a related work, Trimurti showed that anonaine was identical with the alkaloid from the seeds of A. squamosa L. muricine and muricimine, alkaloids isolated from A. muricata, are of a different structure but the researchers are in agreement that all four alkaloids are of the aporphine type.
Leaves of Anona reticulata L. (custard apple) were gathered air-dried for three days and then powdered. Extraction with 95% ethanol yielded a brownish syrupy residue. When acidified and treated with water, the resinous matter was separated. The aqueous acid solution was further extracted using base-organic solvent acid procedures. Tests on the acid extract with Mayer?s reagent gave a positive indication for the presence of alkaloid. The resinous matter, however, have negative results with alkaloidal reagents that complete extraction of the alkaloids must have been achieved.
In the thin layer chromatographic analysis of the extracts of anona, atis, and guyabano in hexane:ethyl acetate (1:1) the former gave good elution giving rise to three (3) distinct spots with Rf values of 0.5228, 0.7659, 0.8693. Spectrophotometric analysis of the acid extract gave λmin = 218 nm and λmax = 282 nm.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, 1981.
Keywords: Annonaceae; Annona; Anonas